Moderation effect of impulsivity in the relationship between depression and suicide ideation among late adolescent in Malaysia - A Halim, Mohd Tarmizi; Abdul Kadir, Nor Ba'yah; Ab Rahman, Roseliza Murni; Ibrahim, Norhayati; Ibrahim, Muhamad Ariff (Human Resource Management Academic Research Society, 2020)
Introduction: The increasing prevalence of suicidal behavior among adolescents in Malaysia recorded for the past decades needs further attention and investigation. Past research has suggested that impulsivity serves as a predictor and risk factor for suicidal ideation. The role of impulsivity as a moderator in the relationship between depression and suicidal ideation among late adolescents in Malaysia were understudied. Objectives: This study aims to identify the relationship between impulsivity, depression and suicide ideation and examine the moderation properties of impulsivity in depression and suicide ideation relationships among late adolescents in Malaysia. Methods: A cross-sectional survey was conducted involving 577 respondents recruited among university students who were currently pursuing their study in public universities located in Wilayah Persekutuan Kuala Lumpur and Selangor. The Short Version UPPS-P Impulsive Behaviour Scale (SUPPS-P), Center for Epidemiologic Studies Depression Scale-Revised (CESD-R) and Revised Suicide Ideation Scale (R-SIS) was utilized to obtain the data regarding impulsivity personality trait, depression and suicide ideation respectively. Results and Discussion: Results show that impulsivity correlated positively and significantly with depression and suicide ideation. Impulsivity was also found to moderate the relationship between depression and suicidal ideations. Furthermore, the suicidal individual with high intention to die exhibit impulsivity traits equally to individuals with self-inflicted injury and has no intention to die. Conclusion: In summary, impulsivity personality trait shall be treated as a profound risk factor when combined with depressive symptoms in elevating the probability of suicide among late adolescents. Therefore, impulsivity trait screening should be practiced during the initial clinical interview, especially among high-risk groups.